Enhanced Growth Economic in Medan City Based on Improvement and Development of Micro, Small and Medium Businesses - Fakhrurozi; Rusiadi; Cahyo Pramono (Budapest International Research and Critics University, 2022)
During this time of covid 19, many of the world's economies fell drastically, so one method that can improve the economy of the city of Medan is to make improvements to micro, small and medium enterprises. So, in this paper, a study aims to identify and analyze the development of micro, small and medium enterprises (MSMEs) in supporting economic growth in the city of Medan. One of the business fields that can develop and be consistent in the national economy is Micro, Small, and Medium Enterprises (MSMEs). Micro, small and medium enterprises (MSMEs) are a good forum for job creation planned by the government, private sector, and individual business actors.